2017
DOI: 10.1590/1516-4446-2016-2144
|View full text |Cite
|
Sign up to set email alerts
|

Bipolar disorders: is there an influence of seasonality or photoperiod?

Abstract: Objective: To increase understanding of the influence of photoperiod variation in patients with bipolar disorders. Methods: We followed a sample of Italian bipolar patients over a period of 24 months, focusing on inpatients. All patients admitted to the Psychiatric Inpatient Unit of San Luigi Gonzaga Hospital in Orbassano (Turin, Italy) between September 1, 2013 and August 31, 2015 were recruited. Sociodemographic and clinical data were collected. Results: Seven hundred and thirty patients were included. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 42 publications
1
26
0
Order By: Relevance
“…In line with our hypothesis, the first significant finding consisted in the increased amount of bipolar subjects’ admissions when the mean sunshine hours was longer. This result confirms the role of meteorological variables such as sunshine hours on the admission rates of bipolar subjects when using a different methodology rather that that used in previously published studies [14,16], suggesting that the photoperiod reaches its maximum extension during summer and its minimum during winter in Italy. Importantly, increased sunlight exposure during the day has been hypothesized to play a stabilizing effect on specific neurotransmitters levels such as monoamines that are relevant to mood disorders [6].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In line with our hypothesis, the first significant finding consisted in the increased amount of bipolar subjects’ admissions when the mean sunshine hours was longer. This result confirms the role of meteorological variables such as sunshine hours on the admission rates of bipolar subjects when using a different methodology rather that that used in previously published studies [14,16], suggesting that the photoperiod reaches its maximum extension during summer and its minimum during winter in Italy. Importantly, increased sunlight exposure during the day has been hypothesized to play a stabilizing effect on specific neurotransmitters levels such as monoamines that are relevant to mood disorders [6].…”
Section: Discussionsupporting
confidence: 84%
“…In healthy subjects, environmental variables such as sunlight exposure, photoperiod and solar radiation/insolation can regulate behavior affecting circadian functions and detemine changes of many biological rhythms. Recently, some authors investigated the role of these factors in bipolar patients with significant impact on both the onset and course of BD and consequently on sleep-wake cycle, mood and energy [10,12,13,14,15,16]. Furthermore, certain authors indicated that environmental factors, such as humidity, day length, ultraviolet radiation, temperature, rainfall/atmospheric pressure or airborne allergens exert a significant role on the admission of BD patients, particularly in (hypo)manic phase, or when they exhibit specific symptoms such as psychosis, impulsiveness, and suicidal behavior/aggression [14,17,18,19,20,21,22,23,24,25].…”
Section: Introductionmentioning
confidence: 99%
“…In any case, given the very distinct timing of the spring peak in suicidal mixed mood states, one is tempted to attribute this heightened springtime conflict between polar opposite moods to some kind of pathological transitional state between winter and summer modes of mood and energy regulation (i.e., depression vs. mania). Relevant to this hypothesis of transitions from winter to spring is that many, but not all, studies have found summer peaks in the incidence of mania [reviewed in 65]. …”
Section: Discussionmentioning
confidence: 99%
“…If patients had more than one psychiatric diagnosis, the principal psychiatric condition as diagnosed by the treating psychiatrist, was recorded. According to previous published studies (33, 34), we grouped the diagnosis in four main categories: bipolar and related disorders, depressive disorders, schizophrenia, and related disorders, other psychiatric disorders.…”
Section: Methodsmentioning
confidence: 99%